2009
DOI: 10.1016/j.jvs.2009.03.055
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells associate with neovessels in the media and adventitia of abdominal aortic aneurysms

Abstract: The results support participation of MCs in the pathogenesis of AAA, particularly regarding neovascularization of aortic wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 41 publications
2
51
0
Order By: Relevance
“…This importance of elastin breakdown products stimulating neovascularization (as opposed to just hypoxia from a thickening ILT) may explain, in part, why significant differences in neovascularization were noted between aneurysmal walls and control aorta but not between thick versus thin thrombus covered aneurysmal walls [65] or thrombus covered versus noncovered aneurysmal walls [76]. Faisal et al [73] similarly showed that a laminin peptide found in AAAs, due to release from the degrading ECM, can upregulate uPA and MMP-9 in macrophages.…”
Section: A Unique Role For Matrikines?mentioning
confidence: 99%
See 4 more Smart Citations
“…This importance of elastin breakdown products stimulating neovascularization (as opposed to just hypoxia from a thickening ILT) may explain, in part, why significant differences in neovascularization were noted between aneurysmal walls and control aorta but not between thick versus thin thrombus covered aneurysmal walls [65] or thrombus covered versus noncovered aneurysmal walls [76]. Faisal et al [73] similarly showed that a laminin peptide found in AAAs, due to release from the degrading ECM, can upregulate uPA and MMP-9 in macrophages.…”
Section: A Unique Role For Matrikines?mentioning
confidence: 99%
“…Similarly, proteases, degradation products, antigens, and other soluble biomolecules may be transported radially through the aneurysmal wall toward the adventitia, which can play a major role in arterial responses to disease, including fibroblast activation, neovascularization, immunoinflammation, and fibrosis [78]. It is also likely that the permeability increases as the endothelial lining is lost [76] and the organized structure of the healthy aortic wall is degraded [51]. Along these lines, recent attempts at modeling the thrombus and aneurysmal wall as porohyperelastic structures [86,87] may provide insight into the complex interstitial fluid flows in thrombus-laden AAAs.…”
Section: A Unique Role For Matrikines?mentioning
confidence: 99%
See 3 more Smart Citations